A Surgeon-Centered Neuromuscular Block Protocol Improving Intraoperative Neuromonitoring Outcome of Thyroid Surgery - Lu, I-Cheng; Hsu, Chiung-Dan; Chang, Pi-Ying; Wu, Sheng-Hua; Huang, Tzu-Yen; Lin, Yi-Chu; Ko, How-Yun; Dionigi, Gianlorenzo; Chai, Young Jun; Chiang, Feng-Yu; Kuo, Yi-Wei; Wu, Che-Wei (Frontiers in Endocrinology, 2022)
Background: Neuromuscular block agents provide muscular relaxation for tracheal intubation and surgery. However, the degree of neuromuscular block may disturb neuromuscular transmission and lead to false-negative or weak electromyography responses during intraoperative neuromonitoring during thyroid surgery. This study aimed to investigate a surgeon-friendly neuromuscular block degree titrated sugammadex protocol to maintain both intraoperative neuromonitoring quality and surgical relaxation during thyroid surgery. Methods: A total of 116 patients were enrolled into two groups and underwent elective thyroid surgery with intraoperative neuromonitoring. All patients followed a standardized intraoperative neuromonitoring protocol with continuous neuromuscular transmission monitoring and received 0.6 mg/kg rocuronium for tracheal intubation. After the initial surgical steps of subplatysmal flap creation and separation of the strap muscles to expose the anterior surface of the thyroid gland, patients were allocated into two groups according to the degree of neuromuscular block. The neuromuscular block degree was assessed by the train of four (TOF) count and ratio. Patients in group I received sugammadex 0.25 mg/kg for non-deep neuromuscular block degree (TOF count =1–4). Patients in group II were administered sugammadex 0.5 mg/kg for deep neuromuscular block degree (TOF count = 0). The quality of the intraoperative neuromonitoring was measured using the V1 EMG amplitude. An amplitude less than 500 𝜇V and greater than 500 𝜇V was defined as weak and satisfactory, respectively. Results: The quality of the intraoperative neuromonitoring was not different between groups I and II (satisfactory / weak: 75/1 vs. 38/2, P = 0.14). The quality of surgical relaxation was acceptable after sugammadex injection and showed no difference between groups (55/76 [72.3%] in group I vs. 33/40 [82.5%] in group II, P = 0.23). Conclusions: This surgeon-centered sugammadex protocol guided by neuromuscular block degree (0.5 mg/kg for deep block and 0.25 mg/kg for others) showed comparably high intraoperative neuromonitoring quality and adequate surgical relaxation. The results expanded the practicality of sugammadex for precise neuromuscular block management during monitored thyroidectomy.